(untitled) (Nigerian Journal of Health Sciences, 2024)
Context: The efficacy of ocular surgeries as a treatment option for eye pathologies depends on the knowledge and utilization by the populace which is influenced by a myriad of factors. There is an increasing demand for shared decision-making in clinical guidelines. Therefore, emphasis is placed on increasing patients’ knowledge which can lead to improved decision quality. Aim: This study assessed the knowledge of ocular surgeries as a treatment option among adults in Evbomore Community. Settings and Design: A cross-sectional study was conducted in Evbomore Community, Benin City among 308 adults (p=14.3%). Methods and Material: Multi-stage sampling method was used, employing an interviewer-administered questionnaire. Statistical analysis: Data was analyzed using IBM SPSS version 25.0 and statistical association was considered significant at p<0.05. Results: The respondents had a mean age of 35.9 (SD 12.7) years. Majority (84.4%) were aware of ocular surgeries as a treatment option, however, only 16.2% of participants had good knowledge of ocular surgeries. Increasing educational status (p<0.01) significantly influenced knowledge of ocular surgery. Socioeconomic status was found to be a significant determinant of knowledge of ocular surgery (p= 0.006). Conclusion: Majority of the respondents were aware of ocular surgeries but only a few had good knowledge of the benefits, risks, and complications associated with the surgeries. Level of education significantly influenced knowledge. Health education, campaigns, and screening outreaches that are community-based should be embarked upon to improve the knowledge of respondents to facilitate better decision-making and health outcomes. Keywords: Knowledge, Surgery, Ocular